PENINGKATAN NUMERASI SISWA PADA PEMBELAJARAN MATEMATIKA MELALUI MEDIA PEMBELAJARAN ROMAT DI SDI TEBUIRENG Ir. SOEDIGNO - Kasno, Kris Dwita Putri; Mahsun, Ali (PGMI UNHASY, 2025)
Numeracy skills are related to the capacity for logical thinking and problem solving in everyday life, numeracy skills are an important component in elementary school education. However, elementary school students often have difficulty understanding numeracy concepts such as fractions, especially those at the concrete operational stage. The purpose of this study is to create interactive and visual Roda Matematika (ROMAT) learning resources that will help encourage students to understand the concept of fractions better. This study uses the five-stage ADDIE development paradigm, which consists of the following steps: analyzing, designing, developing, implementing, and evaluating. Forty second-grade students from SDI Tebuireng Ir. Soedigno Jombang, divided into two classes, became the subjects of the study. Numeracy skills tests, interviews, and questionnaires for expert validation are some of the research tools used. Based on the validation results, the Roda Matematika (ROMAT) media was considered feasible with a feasibility percentage of 86% from material experts, 78% from media experts, 90% from learning experts. With an average feasibility of 84.6%, this media was declared very feasible to use. In addition, in the numeracy ability test, there was also a significant difference between the experimental class and the control class, so it can be concluded that the Roda Matematika (ROMAT) learning media is able to improve students' numeracy skills effectively. This study contributes to the development of concrete learning media that are in line with the stages of students' cognitive development and support the improvement of numeracy literacy in elementary education